The Role of Immune Defense in Serratia marcescens Nosocomial Infections - Raheem, Ihsan A.; Abdul , Fatima R.; Subhi, Hanan T. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
Developing resistance mechanisms leads to various nosocomial infections caused by opportunistic bacteria. Serratia marcescens are well known to be opportunistic and are equipped with an armory of virulence factors against host immune response. The study aims to detect the immune defense in patients infected with multidrug-resistant S. marcescens. The study includes 132 clinical samples, including burn, wound, otitis media, and urinary tract infection (UTI) at several hospitals in Baghdad, Iraq. All isolates are identified by cultivation on MacConkey agar, nutrient agar, and blood agar, followed by biochemical tests and assessment with the VITEK 2 compact system. The isolates are tested for antibiotic susceptibility tests, interleukin-12 (IL12) levels, neutrophil ability to phagocytosis, and complement C3 and C4 levels. Out of 120 positive cultures, six isolates are identified as S. marcescens. The urine samples are the most isolated source and a higher level of antibiotic resistance was noticed in ampicillin and cefotaxime (100%), whereas a lower level is in imipenem. Stimulation (p ꞊ 0.005) provided a significant increase in IL-12 production. The infection with the S. marcescens stimulated the neutrophil’s phagocytosis process compared with the control. The interplay role of virulence factors in S. marcescens influences its pathogenesis, antibiotic resistance, and immune response, particularly involving neutrophils and IL-12. Understanding these interactions is crucial for developing effective therapeutic strategies.